Improving Student Engagement and Connection in Online Learning: Part II, Methodologies and Practices - Chang,Xiaohui (2022)
The first article in the series appeared last December. Since then, we have received plenty of feedback from other instructors who are actively engaged in online education. Almost all of them agreed that teaching well online remains a challenging task. In this article, I discussed six specific practices that I have found particularly helpful for online teaching and learning. Practice 1: Adopt a variety of communication methods Practice 2: Create a Q&A Discussion Board Practice 3: Estimate the amount of time taken for each assignment Practice 4: Ensure timely replies Practice 5: Synchronize assignments with the Canvas calendar Practice 6: Reorganize course content
Keywords: Business Analytics